Bihar - A Rapid Private Health Sector Assessment - World Bank (Washington, DC: World Bank, 2022)
There is little current information available on private health facilities in Bihar. Government has little to do with the private sector and no recent attempts have been made to survey the private formal or informal sectors. However, we know that the private sector is the dominant force in health care provision both for outpatient and inpatient services. During site visits to Patna and the neighboring districts, author saw a number of private health clinics clustered by main roads in secondary towns, most of which cater to maternal and child health. Patna is home to a number of impressive private for profit and voluntary facilities. Such facilities have moved in to the fill the vacuum left by a non-performing public sector. In conclusion, the gap between demand and supply has been filled by various private providers, who are seen to be either better or in many cases the only alternative to the public health facilities. They include a range of providers such as informal unqualified providers, Traditional Birth Attendants (TBAs), faith healers, pharmacists or pharmacy assistants in medicine shops, qualified physicians, and Non Government Organization (NGO) clinics and for-profit nursing homes and hospitals. It is important to understand that the private sector does not represent a homogenous group.